PENGGUNAAN STRUKTUR DATA STACK DALAM PEMROGRAMAN C++ DENGAN PENDEKATAN ARRAY DAN LINKED LIST - Setiyawan, Risky Dwi; Hermawan, Doni; Abdillah, Ahmad Fahmi; Mujayanah, Arsil; Vindua, Raditia (JUTECH : Journal Education and Technology, 2024)
The background of this research is based on the importance of efficiency in implementing the Stack data structure, which is widely used in various programming applications such as mathematical expression evaluation, memory management, and undo/redo features. Two common approaches, namely Array and Linked List, each have their advantages and disadvantages in terms of execution efficiency, memory usage, and flexibility. This study compares the implementation of the Stack data structure using these two approaches, focusing on execution time efficiency, memory usage, and size flexibility. Using an experimental method, the implementation was conducted in C++ programming language through scenarios such as mathematical expression evaluation and undo/redo features. The results show that the Array approach is more efficient for static data access, while the Linked List excels in size flexibility and dynamic memory allocation for variable data. The study concludes that the choice of approach depends on the specific application requirements. These findings are expected to assist software developers in selecting the appropriate Stack implementation method.